2020
DOI: 10.1007/s10961-020-09790-w
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external networks, and incubatees’ performance in dynamic environments: entrepreneurial learning’s mediating effect

Abstract: Business incubators (BIs) have gradually evolved to focus increasingly on the development of networks and network functions. However, existing literature indicates that much ambiguity remains regarding the importance and role of cooperation within the incubator networks. In particular, few studies divide incubator networks into internal and external networks to explore how these networks influence the enterprise growth performance (EGP). Based on the social network and organizational learning theories, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 80 publications
3
66
0
1
Order By: Relevance
“…Entrepreneurs' IOL practices can develop over time based on the changing needs of their ventures (Peltier and Naidu, 2012), and a few studies have also pointed to the formal structures that facilitate entrepreneurial ventures' IOL: Leung et al (2019) studied industry peer networks as a specific way of facilitating entrepreneurial ventures' learning from others, illustrating how IOL occurs by combining cooperation and competition between firms in industry peer networks. Fang et al (2010) and Wu et al (2020) studied IOL facilitated by business incubators and how arrangements in business incubators support IOL internally between tenants, as well as with external actors.…”
Section: Interorganizational Learning In Entrepreneurial Venturesmentioning
confidence: 99%
See 3 more Smart Citations
“…Entrepreneurs' IOL practices can develop over time based on the changing needs of their ventures (Peltier and Naidu, 2012), and a few studies have also pointed to the formal structures that facilitate entrepreneurial ventures' IOL: Leung et al (2019) studied industry peer networks as a specific way of facilitating entrepreneurial ventures' learning from others, illustrating how IOL occurs by combining cooperation and competition between firms in industry peer networks. Fang et al (2010) and Wu et al (2020) studied IOL facilitated by business incubators and how arrangements in business incubators support IOL internally between tenants, as well as with external actors.…”
Section: Interorganizational Learning In Entrepreneurial Venturesmentioning
confidence: 99%
“…Research has shown how entrepreneurs leverage interactions in social networks as sources of important resources and knowledge to respond to crises (Kwong et al, 2019;Muñoz et al, 2019), in addition to knowledge already acquired through the venture's experiences (Smallbone et al, 2012). Wu et al (2020) found that the effect of social networks in business incubators was stronger in situations of dynamism and uncertainty, both of which a crisis represents. Hence, crises can perhaps motivate, or even force, organizations to choose to open up and be receptive to learning from and with other organizations (Peronard and Brix, 2019); this leads to the first hypothesis:…”
Section: Entrepreneurship and Interorganizational Learning In Crisesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fayolle et al (2019) showed that the effects differ depending on trainees' personal characteristics and training strategies, which can have varied impacts on learning processes and results. Entrepreneurship learning is conducive to improving students' willingness to start a business and enterprise growth performance (Liu et al, 2019;Wu W. et al, 2020). The development of EE cannot be separated from the development of entrepreneurial teachers.…”
Section: Introductionmentioning
confidence: 99%